Prevalence of hypertension in school going children in tea garden community in Dibrugarh town, Assam, India - Dastidar, Abhijit; Dutta, Smriti P.; Saikia, Hiranya (International Journal of Research in Medical Sciences, 2016)
Background: The disease burden of hypertension among workers in tea gardens is large, despite the community not being obese. Consumption of high quantity of common salt (NaCl) is considered to be the main factor. Therefore it is expected that prevalence of hypertension and level of blood pressure would be higher among these group of children. Hence the present study was taken to determine the prevalence of hypertension in apparently healthy, asymptomatic school children of tea garden workers in the age group of 6-12 years. Methods: Blood pressure was recorded in the right arm in the sitting position by using a standard Hg sphygmomanometer using appropriate cuff sizes. Three readings were taken at an interval of at least 5 minutes and the average of these three readings was considered as the blood pressure of the individual. Average SBP or DBP levels that are greater than or equal to the 95th percentile for sex, age, and height was taken as hypertension. Results: The prevalence of systolic, diastolic and both systolic and diastolic hypertension are 3.86%, 1.71% and 4.29% and 2.62%, 0.37% and 5.24% in boys and girls respectively and the overall prevalence of hypertension was found to be 9.0% (systolic 3.2%, diastolic 1.0% and systolic and diastolic 4.8%). Conclusions: The high risk children need to be considered for close follow ups for modification of risk factors by advising lifestyle changes like reduction in intake of salt.